Severe respiratory distress secondary to pharyngeal perforation during endoscopic gastrostomy tube removal: a clinical case report - Siblani, Dima; Stiel, Laure; Husson-Wetzel, Stéphanie; Barsotti, Pierre (Frontiers in Gastroenterology, 2023)
We present a case of a 60-year-old patient with advanced COPD who underwent endoscopic removal of her gastrostomy feeding tube, which had been inserted to optimize her nutritional status prior to lung transplantation. However, during the procedure, the device became accidentally blocked at the pharyngeal level, causing a transmural laceration and resulting in rapid respiratory distress and subcutaneous emphysema. As a result, the patient required intubation. After stabilization, a new attempt was made to retrieve the device endoscopically, but this was unsuccessful. A CT was performed, which showed the blocked piece in the cervical wall, diffuse subcutaneous emphysema, large pneumomediastinum, and a left pneumothorax. The patient was then taken to the operating room for surgical retrieval of the trapped parts, which involved a left pharyngeal incision, and retrieval of the trapped parts. The patient was subsequently transferred to the ICU, where she was successfully weaned off the ventilator and extubated one week later.